Do enlace ao refazer-se fita: o divórcio e seus desdobramentos na perspectiva dos filhos - Franco, Marina Prado (2019)
Divorce has been increasing in the last decade in Brazil and implies consequences for all members of the family system, especially for the children. This study aimed to understand how the child perceives the changes in his / her life in the family environment after parental divorce. A qualitative case study was carried out with parents and their 7-year-old daughter, consisting of a semi-structured interview with each of the parents and, with the child, an adaptation of the Structured Family Interview (FERES-CARNEIRO, 1997) by the author of the study in question. The parents were separated about 17 months ago, with the parents coming out of the first divorce. The results were submitted to content analysis of the information from the interviews with the parents and the child. From this analysis, the following categories were constructed: separation process, parental health, parenthood after divorce, relationship between former spouses, changes in routine and family environment. Studies have confirmed that separation itself is not the main factor influencing adjustment problems that children with divorced parents may have, but rather the way to conduct this transition phase by parents. Parental well-being, parental practices responsive to the needs of the child, and lack of interparental conflict are the main protective factors for child adaptation to this process. In the study in question, in relation to the separation process itself, the child has a clear understanding of what happened and maintains a positive view about his or her life after the divorce, reports only one longing for the father, for living away. The way the parents dealt with the divorce process, which was friendly and concerned about their daughter's wellbeing, enabled this adaptive response. Regarding the health of the parents, although the father lives the separation with suffering, having resorted to professional support of psychologist and psychiatrist, this does not seem to have affected the child, who does not comment on the parental malaise. As for the relationship between parents and changes in the routine of the family environment, the daughter also presents adaptive responses, focusing on the positive side of new situations. The only change she highlights is the feeling of sadness about being away from her father. She sees the parents' relationship with friendly conversation when they meet. Thus, there is a possibility of healthy adaptation for preschool children facing parental divorce when parental care with quality, protection and affection for the child and good relationship between the parents have a function of protective factors